Dasar Alkitabiah Tentang Pertumbuhan Gereja Sebagai Landasan Pertumbuhan Jemaat - Zafnat Paaneah, I Gede Agus (JURNAL ILUMINASI, 2023)
The early church, or the church during the time of the apostles, was a church that grew in quantity and quality. Even though in general the environment around it was hostile towards its presence, this situation did not in any way reduce or hinder the growth that occurred in it. The church carries out its service duties in the concrete world against the backdrop of a dynamic life context. In this regard, the church is required to proactively understand and guide members of the congregation to live a life of faith in the Lord Jesus Christ correctly in the struggles of everyday life. In this case, the church is required to be able to understand and answer the concrete needs of the church community and the environment in which the church is located. One of the urgent needs is the implementation of the Great Commission by empowering the laity in their diversity to become a strong force extraordinary in church growth. It cannot be separated from the role of lay people in the growth of a church. Discipleship also plays an equally important role. Because discipleship lies at the center of the church's goal, which is to make all people like Christ.